Correlation between head posture and proprioceptive function in the cervical region - Yong, Min-Sik (J Phys Ther Sci, 2016)
[Purpose] The aim of the present study was to investigate correlation between head posture and proprioceptive function in the cervical region. [Subjects and Methods] Seventy-two subjects (35 males and 37 females) participated in this study. For measurement of head posture, the craniovertebral angle was calculated based on the angle between a horizontal line passing through C7 and a line extending from the tragus of the ear to C7. The joint position sense was evaluated using a dual digital inclinometer (Acumar, Lafayette Instrument, Lafayette, IN, USA), which was used to measure the joint position error for cervical flexion and extension. [Results] A significant negative correlation was observed between the craniovertebral angle and position sense error for flexion and extension. [Conclusion] Forward head posture is correlated with greater repositioning error than a more upright posture, and further research is needed to determine whether correction of forward head posture has any impact on repositioning error.